2004
DOI: 10.1002/j.1939-4640.2004.tb02805.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Centrifugation Before Freezing on Boar Sperm Cryosurvival

Abstract: Current protocols for boar sperm cryopreservation require the centrifugation of semen in order to separate sperm cells from the seminal plasma. This study evaluated the influence of different centrifugation regimes on both sperm recovery and yield (percentage of viable sperm with an intact acrosome relative to the initial sperm population) after centrifugation (experiment 1) as well as the influence of different centrifugation regimes on boar sperm cryosurvival (experiment 2). In both experiments, sperm-rich f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 31 publications
7
75
0
16
Order By: Relevance
“…Similar results were found by Jimenez-Rabadan et al (2012), who selected goat semen in a solution of silica coated with silane specific for bovines. The recovery rates can be altered by several factors, among them: quality of semen before centrifugation (Alvarez et al, 2010;Martinez-Alborcia et al, 2013), caution at the time of deposition of the semen sample at the top of the gradient selection column (Thys et al, 2009), TM increase after sperm selection, and time and intensity of centrifugation force (Carvajal et al, 2004). Martinez-Alborcia et al (2013) hypothesized that non-functional spermatozoa saturate the interface between the semen and the colloid, obstructing the passage of functional spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found by Jimenez-Rabadan et al (2012), who selected goat semen in a solution of silica coated with silane specific for bovines. The recovery rates can be altered by several factors, among them: quality of semen before centrifugation (Alvarez et al, 2010;Martinez-Alborcia et al, 2013), caution at the time of deposition of the semen sample at the top of the gradient selection column (Thys et al, 2009), TM increase after sperm selection, and time and intensity of centrifugation force (Carvajal et al, 2004). Martinez-Alborcia et al (2013) hypothesized that non-functional spermatozoa saturate the interface between the semen and the colloid, obstructing the passage of functional spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez-Alborcia et al (2013) hypothesized that non-functional spermatozoa saturate the interface between the semen and the colloid, obstructing the passage of functional spermatozoa. Carvajal et al (2004) tested several swine semen centrifugation protocols and suggested that the intensity of the centrifugation force is more important than the centrifugation time in the sperm recovery rate. This fact would explain the higher recovery in the methods employing silica colloidal-PVP, considering that the intensity of the g force was of 900 compared to 300 in the methods using silica colloidal-silane.…”
Section: Discussionmentioning
confidence: 99%
“…The straws were then plunged into the liquid nitrogen. After thawing the straws at 37°C for 20 sec [5], thawed semen was evaluated for sperm motility [13], morphological defect, viability by eosin-nigrosin staining [4], and plasma-and acrosomalmembrane integrities. Sperm plasma-membrane integrity was assessed using 6-carboxyfluoresceindiacetate (6-CFDA; Sigma-Aldrich)/propidium iodide (PI; Sigma-Aldrich) fluorescent staining [12] and analyzed by flow cytometry.…”
mentioning
confidence: 99%
“…Indeed, our results show a positive effect of temperature on SOD and GPX1 activity that at the same time seems to have an indirect effect on sperm quality likely to maintain a constant fitness for reproductive success ( Figure 6). Addition of SP in a range of 5-50% (v/v) to the extender minimized cryopreservation-induced membrane damage [5,9,38] or early onset of acrosome responsiveness post-thaw [16,38] due to stabilizing proteins or antioxidant enzymes in SP that provide protection to the sperm cells [6,13,31]. Results in our study indicate that addition of SP to frozen-thawed semen ameliorated the negative effects of cryopreservation compared with control sperm as reflected in higher EN as well as HOST percent values (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 99%